The Worthy Research Approaches to Endangered Languages - Iskandarsyah Siregar (Formosa Journal of Sustainable Research, 2023)
Research plays a crucial role in preserving languages by enhancing their use as a means of knowledge. Language serves various functions, including cognitive, enabling users to express thoughts. This research employs a combination of analysis methods, incorporating field data collection, classification, analysis, and concluding. It is important to integrate this data with information obtained from reference literature. Both qualitative and quantitative methods are utilized to achieve optimal outcomes at each stage of the research process. Preserving a language's distinct characteristics is essential for it to continue serving as a medium of knowledge. One effective approach for researching endangered languages is Sociosemiotic or Social Semiotic analysis. Sociosemiotics provides a valuable framework for understanding the dynamic signs and symbols present within a society. These variables of signs and symbols are crucial for effectively analyzing problems and developing solutions. The most important thing is to find the authenticity of the original form of the endangered language, see the actual conditions of the endangered language, investigate the impact of the endangered language as seen from the decrease in a variable in the communication habitat of its users, and formulate a preservation/preservation model for the endangered language